Mass spectrometric comparison of swift heavy ion-induced and anaerobic thermal degradation of polymers. (March 2018) - Lima, V.; Hossain, U.H.; Walbert, T.; Seidl, T.; Ensinger, W.
Abstract: The study of polymers irradiated by highly energetic ions and the resulting radiation-induced degradation is of major importance for space and particle accelerator applications. The mechanism of ion-induced molecular fragmentation of polyethylene, polyethyleneimine and polyamide was investigated by means of mass spectrometry and infrared spectroscopy. The results show that the introduction of nitrogen and oxygen into the polymer influences the stability rendering aliphatic polymers with heteroatoms less stable. A comparison to thermal decomposition data from literature reveals that ion-induced degradation is different in its bond fracture mechanism. While thermal degradation starts at the weakest bond, which is usually the carbon-heteroatom bond, energetic ion irradiation leads in the first step to scission of all types of bonds creating smaller molecular fragments. This is due to the localized extreme energy input under non-equilibrium conditions when the ions transfer kinetic energy onto electrons. These findings are of relevance for the choice of polymers for long-term application in both space and accelerator facilities. Highlights: Particle accelerator experiments give information about polymer degradation. High energy ions irradiation simulates use in space and accelerator application. Heteroatoms like nitrogen and oxygen introduce predefined scission points. Ion-induced degradation shows a different behavior than thermal decomposition.